Integrating plasticity into precision psychiatry - Igor Branchi (European Psychiatry)
Understanding transitions from psychopathology to well-being is crucial for promoting recovery. Plasticity – the ability to modify brain functioning and mental states – is increasingly recognized as essential because it enables the reorganization of neural and mental processes underlying such transitions. Recently, a network-based approach that operationalizes plasticity, and the ability to transition to well-being, as the inverse of the connectivity strength within the symptom network has been proven effective in predicting both the likelihood and timing of recovery from major depressive disorder. This innovative method to measure plasticity is opening new avenues for timely diagnosis, patient stratification, and targeted, individualized treatment of mental illness. Overall, integrating the assessment of plasticity levels into precision psychiatry holds significant potential for developing novel and effective personalized therapeutic strategies in psychiatry.